Does international outsourcing depress union wages? - Sebastian Braun; Juliane Scheffel (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
In this paper, we provide first empirical evidence on the effect of outsourcing on union wages using linked employer-employee data for Germany. We find that low skilled workers experience a decline in the union wage premium when working in industries with high outsourcing intensities. The finding applies to both firm- and sector-level agreements. Hence, outsourcing appears to deteriorate the bargaining position of unions. Outsourcing is not found to have a negative effect on the wages of low skilled employees not covered by collective bargaining agreements. While wages of medium skilled workers are largely unaffected by outsourcing, high skilled workers see their wages rise in industries with a high level of outsourcing. There is no interaction between coverage and outsourcing for these skill groups.
Keywords: F16; J51; L24; 330; Collective Bargaining; International Outsourcing; Union Wages; Outsourcing; Offshoring; Tariflohn; Tarifpolitik; Lohnstruktur; Qualifikation; Deutschland